Implications of digitalization on the persistence of startups - Débora De-Esteban-Escobar; Carmen de Pablos Heredero; José Luis Montes Botella; Francisco José Blanco Jiménez (Administrative Sciences, 2024)
Digitalization is a transformative phenomenon catalyzing innovative paradigms and operational methodologies within the realm of business, with a pronounced impact on nascent enterprises, notably startups. The aim of this paper is to ascertain the influence of digitalization and the effects of the different sociodemographic variables, both internal and environmental, as key driving elements in the probability of a company's success and as indicators of business persistence and growth. Taking a representative sample of entrepreneurs from the Community of Madrid, Spain, a statistical structural equation model (SEM) is built. The results show the importance that the degree of adaptation of the startup to digitization acquires in persistence, the effort to generate inter-entrepreneurship within the company, the preparation of the promoting team, their work skills, good practices, and the influence of environmental variables. This study contributes to dispelling the great uncertainty that afflicts entrepreneurs and making them understand the importance of innovation, training, and continuous updating, expansion, and renewal of knowledge and especially the value of learning about applications of new technologies, the transformation of processes within a business model, and the correct adaptation to an environment that is constantly changing.
Keywords: 350; business incubators; business success; digital transformation; entrepreneurship; innovation